BIFoR FACE: Water–soil–vegetation–atmosphere data from a temperate deciduous forest catchment, including under elevated CO2. Issue 3 (15th March 2021) - MacKenzie, A. Rob; Krause, Stefan; Hart, Kris M.; Thomas, Richard M.; Blaen, Phillip J.; Hamilton, R. Liz; Curioni, Giulio; Quick, Susan E.; Kourmouli, Angeliki; Hannah, David M.; Comer‐Warner, Sophie A.; Brekenfeld, Nicolai; et al.
Abstract: The ecosystem services provided by forests modulate runoff generation processes, nutrient cycling and water and energy exchange between soils, vegetation and atmosphere. Increasing atmospheric CO2 affects many linked aspects of forest and catchment function in ways we do not adequately understand. Global levels of atmospheric CO2 will be around 40% higher in 2050 than current levels, yet estimates of how water and solute fluxes in forested catchments will respond to increased CO2 are highly uncertain. The Free Air CO2 Enrichment (FACE) facility of the University of Birmingham's Institute of Forest Research (BIFoR) is the only FACE in mature deciduous forest. The site specializes in fundamental studies of the response of whole ecosystem patches of mature, deciduous, temperate woodland to elevated CO2 (eCO2 ). Here, we describe a dataset of hydrological parameters – seven weather parameters at each of three heights and four locations, shallow soil moisture and temperature, stream hydrology and CO2 enrichment – retrieved at high frequency from the BIFoR FACE catchment. Abstract : The tissue and data pipelines for the BIFoR FACE catchment.